Jumpstarting Health With a 15-Day Whole-Food Plant-Based Program. Issue 3 (May 2022) - Friedman, Susan M.; Barnett, Carol Hee; Franki, Robert; Pollock, Bruce; Garver, Beth; Barnett, Ted D.
The 15-day Jumpstart was developed as an evidence-based, affordable, standardized, replicable, and scalable program, designed to demonstrate quickly to patients that changing what they eat can improve their health. The program was designed using the principles of the self-determination theory of motivation and personality. Patients were instructed to eat an Esselstyn-compliant, whole-food plant-based diet consisting of vegetables, fruits, whole grains, and legumes. Of the 389 participants in the program from September 2018 to February 2020, average weight loss was 5.8 pounds (7.3 for those whose body mass index was >30), average systolic blood pressure drop was 6.8 points (16.8 points for those with systolic blood pressure >140), average drop in cholesterol was 26 points (44 points for those with a cholesterol >200), average drop in low-density lipoprotein was 19 points (33 points for those with a low-density lipoprotein >100), and average drop in fasting blood sugar was 5.1 points (28.4 points for those starting in the diabetic range); P value was <.005 for fasting blood sugar and <.001 for all other comparisons. A 15-day program that helps patients adopt an Esselstyn-style whole-food plant-based diet, through education, individualized medical feedback, social support, and facilitated small group work, rapidly improves health.